Methods for imaging the structure and function of living tissues and cells: 1. Optical coherence tomography - Tadrous, Paul J. (The Journal of pathology, 2000)
This is the first in a series of review articles which aim to present a concise and systematic overview of the principles, limitations, advantages, and uses of some of the more important recently developed techniques capable of imaging living histology. Optical coherence tomography (OCT) is now an established optical biopsy method, imaging 2–3 mm into opaque tissue. It is analogous to optical ‘ultrasound’ but has an outstanding resolution, being capable of imaging single cells in the intact animal via a surface, intravascular or endoscopic approach. Both two‐dimensional (2D) and three‐dimensional (3D) image datasets can be acquired and studied over time (4D imaging) in the live animal or human subject without the need to remove tissue or perform any tissue processing or staining. It has been used in ophthalmology, gastrointestinal tract (GI) studies, gynaecological tract investigation, and endovascular imaging, to name but a few areas. A degree of differential tissue contrast information can also be gleaned, since different tissue components give different OCT reflectivity signals such that adipose, muscle, collagen, and elastic components may all be resolved without staining. Continuing developments include faster data acquisition for real‐time recording and Doppler OCT for more functional imaging. Copyright © 2000 John Wiley & Sons, Ltd.